Simple and secure device authentication mechanism for smart environments using Internet of things devices. (9th August 2020) - Hussain, Muzzammil; Jain, Usha
Summary: Enormous growth in digital electronics technology has paved path for the development of advanced networks, and smart environment is one among them. Smart environment is a network of smart devices connected to provide comfort, security, remote access and many more to end‐users. Devices in smart environments usually collect very sensitive data of the end‐users and disseminate it as required. The privacy of the end‐user has to be ensured in these applications, and security becomes a prime concern. The security system in smart environments has to ensure privacy and need to be more resource‐aware. An efficient authentication mechanism can ensure the privacy of end users and secrecy of the sensitive data; it may avoid unauthorized access of data and resources, ensuring privacy and security. In this paper, we proposed a mechanism for device authentication which enables smart devices to mutually authenticate each other. The proposed mechanism enables smart devices to acquire security credentials from the server and use these credentials to authenticate each other. The mechanism used exclusive OR (XOR), concatenation, one‐way hash, and symmetric key encryption techniques. The security analysis of the mechanism is done and proved that the mechanism is secure. The performance analysis proved that the computational and communications overheads are 8% less than existing mechanisms and storage overhead is also least. Abstract : Proposed protocol for mutual authentication of smart devices in smart environment.